BEKERJA KELUAR NEGERI SECARA LEGAL DAN AMAN - Wahyu Hariadi; Prosawita Ririh Kusumasari; Ferryani Krisnawati (Department of Public Administration, University Wijaykusuma Purwokerto, 2024)
The demands of an increasingly modern era make the needs move very quickly to affect income and employment. There are some Indonesians who choose to work abroad to meet their needs and help their families. This legal counseling aims to provide understanding to students, parents, teachers, the elderly, candidates for employment with disabilities and all other levels of society who may be vulnerable to crime in prospective workers abroad so as to gain a legal understanding of working abroad legally and safely. It is hoped that the community can participate in developing and maintaining what is good and realize that goodness in daily life wholeheartedly, becoming a habit that is continuously practiced and carried out every day. Ease of legal understanding of working abroad legally and safely.